2016
DOI: 10.1159/000449024
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes in EGFR Mutation-Positive Lung Cancer Patients Treated with Gefitinib until or beyond Progression

Abstract: Background: Discontinuation of gefitinib treatment is often accompanied by a disease flare. Some studies have demonstrated a benefit of the use of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKI) beyond progression; however, long-term results of these investigations remain limited. Patients and Methods: We observed 70 patients with EGFR-mutated (EGFR-M+) non-small cell lung cancer (NSCLC) receiving single-agent gefitinib in a routine clinical setting; 56 patients were experiencing RECIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…This result supports the clinical findings that treating with gefitinib post-progression may still provide patients with a benefit [26]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result supports the clinical findings that treating with gefitinib post-progression may still provide patients with a benefit [26]. …”
Section: Discussionsupporting
confidence: 88%
“…Our results also indicate that, although no further shrinkage is gained from continuing on gefitinib, post 8 weeks, the re-growth rate of the resistant clone appears to be slower than that observed for doublet chemotherapy. This result supports the clinical findings that treating with gefitinib post-progression may still provide patients with a benefit [26].…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, epidermal growth factor receptor (EGFR) mutations, such as exon 19 deletion and L858R point mutation, are well recognized as driver mutations and promising predictors of the efficacy of EGFR tyrosine kinase inhibitors (TKIs), such as gefitinib, erlotinib, and afatinib, in NSCLC patients harboring EGFR mutations [3][4][5][6][7]. In addition, EGFR-TKIs are recommended for elderly people [8][9][10] and they are effective regardless of the treatment timing in patients with NSCLC harboring EGFR mutations [11,12]. Recently, a large cohort study reported that gefitinib therapy resulted in a 5-year survival rate of approximately 20% in NSCLC patients harboring…”
Section: Introductionmentioning
confidence: 99%
“…Most studies enrolled patients within the past 20 years and all studies were published within the past 10 years. There were 13 studies which evaluated ppPFS (1,758 patients) ( 17 20 , 23 27 , 30 , 31 , 36 , 37 ), 20 studies which evaluated ppOS (8,271 patients) ( 13 , 15 17 , 19 , 21 , 23 , 24 , 27 , 28 , 30 , 32 37 , 39 , 41 , 44 ), and 12 studies evaluated OS from initiation of drugs (1,579 patients) ( 14 , 15 , 18 , 22 , 25 , 32 , 34 , 38 , 40 43 ). The drugs provided to the TBP groups fell into four categories: 14 studies used EGFR TKIs (43.8%) ( 13 , 14 , 17 19 , 22 , 23 , 25 , 26 , 29 , 30 , 32 , 36 , 44 ), 4 employed ALK TKIs (12.5%) ( 15 , 16 , 34 , 35 ), 10 studies used immunotherapy (31.3%) ( 28 , 31 , 33 , 37 43 ), and 4 articles used anti-angiogenesis (12.4%) ( 20 , 21 , 24 , 27 ).…”
Section: Resultsmentioning
confidence: 99%